Cytokine landscapes of pregnancy: mapping gestational immune phases - Sulagna Dutta; Pallav Sengupta; Fong Fong Liew (Gynecology and Obstetrics Clinical Medicine)
Background Synchronised physiological adaptations occur during pregnancy to achieve systemic, immune and neuroendocrine equilibrium in the mother’s body, allowing semiallogenic fetal growth.Main text Depending on the cytokine profile alterations occurring through pregnancy, the latter can be divided into three distinct phases. In the first immunological phase of pregnancy, proinflammatory cytokines promote inflammatory reactions needed for implantation. In the second phase, a possible change from proinflammatory to anti-inflammatory cytokines creates a symbiosis between maternal and fetal components, ensuring fetal development. In the third phase, inflammatory and cytolytic cytokines operate again to reinforce an inflammatory environment for parturition. The article offers a detailed account of immune adaptations during pregnancy and highlights the distinctive cytokine profiles that mark each phase.Conclusion By providing a simplified depiction of pregnancy phases based on cytokine profiles, the article aims to inspire more research in reproductive immunology and improve the management of pregnancy-related inflammation and infection.